2022
DOI: 10.3390/jcm11216383
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Patients Treated for Renal Cell Carcinoma: A Systematic Literature Review

Abstract: (1) Background: The incidence of psychological distress and its impact on renal cell carcinoma (RCC) patients is unclear. Our aim was to analyze the literature regarding the prevalence of psychological distress and its impact on patients with non-metastatic or metastatic RCC; (2) Methods: A systematic search of five databases was performed. Studies were considered eligible if they included patients with RCC, had a prospective or retrospective design, and assessed anxiety, depression, or psychological distress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…These results support the role of inflammation in depression associated with malignancy and are the first to characterize this relationship in RCC. [3,4,7,32] Importantly, our results also demonstrated that patients with elevated CRP experienced a 3.53 increased odds of reporting clinically significant improvement postnephrectomy. RCC is unique in being one of the few cancers where CRP can be expressed directly by the tumor and surrounding kidney tissue.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These results support the role of inflammation in depression associated with malignancy and are the first to characterize this relationship in RCC. [3,4,7,32] Importantly, our results also demonstrated that patients with elevated CRP experienced a 3.53 increased odds of reporting clinically significant improvement postnephrectomy. RCC is unique in being one of the few cancers where CRP can be expressed directly by the tumor and surrounding kidney tissue.…”
Section: Discussionsupporting
confidence: 60%
“…[ [3][4][5] The reported level of depression in kidney cancer is greater than the pooled prevalence in various cancer subtypes, reaching as high as 19.7% with up to 77.6% of patients with nonmetastatic RCC experiencing depressive symptoms. [6,7] Cancer-related depression is associated with elevated mortality, increased medical nonadherence, and higher treatment costs in various malignancy subtypes including kidney, lung, breast, and brain cancers. [8][9][10] Over the past few decades, various studies suggest that inflammatory pathways may play a key role in the pathophysiology of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, kidney cancer survivors spend a lot of time sedentary, which is defined as any behavior, including sitting, reclining, or lying down, performed during waking hours. Sedentary behavior is linked to adverse health outcomes for kidney cancer survivors, including decreased physical functioning, increased pain and fatigue, decreased well-being, and reduced QoL (Tabaczynski,et al [16]) Furthermore, sleep disturbances are also one of the symptoms most cited by cancer patients during and after treatment [17,18]. Therefore, better sleep quality and longer sleep duration are associated with positive health and well-being and are fundamental to maintaining QoL during the process.…”
Section: Quality Of Life Of Patients With Crcmentioning
confidence: 99%
“…19 Furthermore, psychiatric illnesses have been linked to worse clinical outcomes. 20 In response to this multifaceted challenge, we developed a mobile health (mHealth) application specifically tailored to patients with advanced RCC receiving ICI and VEGFR-TKI combination therapies and assessed the acceptance and feasibility of such an intervention. This innovative platform integrates personalized educational resources guiding diagnosis, prognosis, therapy, therapy-related AEs, and quality-of-life reporting tools to holistically support and address patient's needs.…”
Section: Introductionmentioning
confidence: 99%